HEPATITIS B AWARENESS AND VACCINATION STATUS AMONG STUDENTS OF A MEDICAL COLLEGE IN KPK PESHAWAR (The Research of Medical Science Review, 2024)
Background. Hepatitis B virus (HBV) is a fatal infection and a notorious occupational hazard for health care professionals including medical students. Methods. A cross- sectional study was conducted at Pakistan International Medical College (PIMC), to evaluate the knowledge and awareness about Hepatitis B, Hepatitis B vaccination status and the reason for not getting vaccinated among the 2 nd year and 3 rd year medical students. Results. The present study reveals surprising results and raises issues about the high number of medical students that are not vaccinated which puts them at higher risk of being infected in the future. Another important issue is that medical students lacked awareness about Hepatitis B vaccine. The students have not been totally educated about the seriousness of the situation which requires the need of additional HBV vaccination awareness.